Activation of the adenovirus major late promoter by transcription factors MAZ and Sp1. - Parks, C L (1997)
Multiple binding sites for the transcription factors MAZ and Sp1 within the adenovirus type 5 major late promoter have been identified by DNase I protection studies. In the proximal region of the promoter, both MAZ and Sp1 interact with GC-rich sequences flanking the TATA box. Two MAZ binding sites are centered at -18 and -36 relative to the transcriptional initiation site. Sp1 bound only to the -18 GC-rich sequence. Several sites of interaction were also evident in the distal region of the promoter. Both MAZ and Sp1 interacted with a sequence centered at -166, and MAZ bound weakly to an additional site centered at -130. Overexpression of MAZ or Sp1 activated expression from the major late promoter in transient expression assays. Mutational analysis of the GC-rich sequences in the major late promoter suggested that a primary target of MAZ activation is the GC-rich sequences flanking the TATA sequence, whereas Sp1 requires the distal GC-rich sequence elements to stimulate gene expression. This activation is enhanced by the adenovirus E1A protein, and evidence for interaction between E1A and both transcription factors was obtained by using an immunoprecipitation assay. Activation by MAZ and Sp1 also was observed in transfection studies using the complete adenovirus type 5 genome as the target. Increased levels of late mRNA from both the L1 and L5 regions were observed when MAZ or Sp1 expression plasmids were transfected with viral DNA. Unexpectedly, activation of the major late promoter by MAZ and Sp1 was detected irrespective of whether the viral DNA could replicate.